2020
DOI: 10.1111/jfs.12784
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella enteritidis and Salmonella typhimurium in foods using a rapid, multiplex real‐time recombinase polymerase amplification assay

Abstract: Salmonella has been recognized as a major foodborne pathogen for humans and animals. In this study, a multiplex real‐time recombinase polymerase amplification (RPA) was developed for simultaneous detection of Salmonella enterica serovars, Salmonella enteritidis and Salmonella typhimurium, from chicken, eggs, lettuce, and papaya. The reaction was performed for 20 min at 35°C, and the detection limit of the assay was 102 CFU/ml for pure culture. In food application, the limit of detection (LOD) of S. enteritidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…30 In another study, the same observation applied to lettuce where spiked lettuce was found slightly decreased sensitivity compared to that performed in tube without enrichment. 32 Chicken meat debris contain biological con-taminants, such as blood, skin, and fats, and these might negatively affect RPA reaction. 33 However, the amplification efficiency of our microfluidic device on chicken meat was not largely reduced when compared to that on lettuce, which was probably due to the relatively pure bacterial culture with much less skin residues left after paper filtering.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30 In another study, the same observation applied to lettuce where spiked lettuce was found slightly decreased sensitivity compared to that performed in tube without enrichment. 32 Chicken meat debris contain biological con-taminants, such as blood, skin, and fats, and these might negatively affect RPA reaction. 33 However, the amplification efficiency of our microfluidic device on chicken meat was not largely reduced when compared to that on lettuce, which was probably due to the relatively pure bacterial culture with much less skin residues left after paper filtering.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Integration of RPA with other detection strategies such as lateral flow [ 114 ], real-time fluorescent detection [ 113 ], and microfluidic [ 115 ] was found to be a success. As soon as their inception, RPA-based methods have been applied in the detection of Salmonella in food samples [ 116 , 117 , 118 ]. Since the success of the isothermal amplification method for Salmonella detection, the RPA system is likely the most convenient choice for point of care application due to its short turnaround time, simple implementation, and minimum sample preparation [ 119 ].…”
Section: Detection Of Salmonellamentioning
confidence: 99%
“…5 Methods based on molecular biology include polymerase chain reaction (PCR), 6 real-time PCR, 7 multiplex PCR, 8 loop-mediated isothermal amplification (LAMP), 9 rolling circle amplification (RCA), 10 and recombinase polymerase amplification (RPA). 11 Although molecular biology methods have high sensitivity, they require specialized equipment and skilled technicians to carry out complex operation procedures.…”
Section: Introductionmentioning
confidence: 99%